Educomunication: Student reporter and the production of audiovisuals - Silva, Nayra Grazielle da; Medeiros, Liziany Müller; Bervig, Aline Andressa; Contreras, Patrício Orozco-; Rosa, Luiz Henrique Carvalho; Bedin, Daiane Teresa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The student reporter will act as agent builder and mediator of knowledge, which will build and collect information and share it in order to contribute to the community. The objective was to evaluate the potential of audiovisual through the mediation of student reporter for the promotion of a teaching-learning. Qualitative and participatory methodology was developed through observation and analysis of teaching and learning in communities generated from views of audiovisual mediated student-reporter process. From this idea were produced tree (3) for the audiovisuals Centro de Ciências Rurais, Universidade Federal de Santa Maria: one (1) Teacher training videoaula to the Center of Rural Sciences in the use of Moodle Learning Platform for Education; One (1) documentary about receiving students of Family Agriculture in Distance Learning mode; One (1) audiovisual tutorials for using the tools in the Resource and Activities Teaching and Learning Platform Moodle. As conclusion it was observed that the use of audiovisual contributed to the process of teaching-learning communities where they were applied.